2005
DOI: 10.1097/01.ccm.0000150956.90030.23
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the August 2003 blackout on the New York City healthcare delivery system: A lesson for disaster preparedness

Abstract: The blackout dramatically increased EMS and hospital activity, with unexpected increases resulting from respiratory device failures in community-based patients. Our findings suggest that current capacity to respond to public health emergencies could be easily overwhelmed by widespread/prolonged power failure(s). Disaster preparedness planning would be greatly enhanced if fully operational, backup power systems were mandated, not only for acute care facilities, but also for community-based patients dependent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 3 publications
1
62
0
1
Order By: Relevance
“…Many of the calls were due to respiratory device failure, with the recognition that a widespread prolonged outage could have easily overwhelmed EMS's ability to respond. 16 Clearly, there will be far less impact when the capabilities of the response team far exceed the needs of those most affected.…”
mentioning
confidence: 97%
“…Many of the calls were due to respiratory device failure, with the recognition that a widespread prolonged outage could have easily overwhelmed EMS's ability to respond. 16 Clearly, there will be far less impact when the capabilities of the response team far exceed the needs of those most affected.…”
mentioning
confidence: 97%
“…Most of these studies focus on the increased use of various health-care sectors during the blackout. For example, an increase in calls to 9-1-1 and emergency services, [3][4][5] including a poison control center, was noted. 6 Klein et al documented that while the power outage increased the utilization of hospitals' emergency services, the effective operation of hospitals was compromised by the loss of power.…”
mentioning
confidence: 99%
“…A quarter of the patients in this survey utilized home oxygen programs. Having sufficient oxygen stores is one of the top concerns for hospitals in an emergency [13, 14]. Experience has shown that during electrical outages, regardless of whether the extended outage is caused by natural disaster, individuals on home oxygen therapy flock to hospitals due to not having a backup generator to run their concentrator units or due to not having enough backup oxygen canisters [13-15].…”
Section: Discussionmentioning
confidence: 99%